2012
DOI: 10.2478/v10172-011-0158-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Wear Mechanisms in Sintered Fe-1.5 Wt % Cu Alloys

Abstract: In this research, increasing amount of ultimate tensile strength and hardness in sintered Fe-1.5 Wt % Cu alloys is observed with increasing the density. The influence of different applied pressure of 300, 450, 600 and 750 MPa on porosity and wear behavior has been also studied.Cross-section micrographs of worn surfaces show that the pores are closed by plastic deformation or oxides and metallic particles after the wear test. According to the wear test results, specimens with 14 vol. % porosity are more wear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…4) suggests the presence of magnetite and hematite in the structure. Mazahery et al have reported that ferrous materials have shown the presence of oxides, which is an implication of oxide wear mechanism [33]. In the current study, high concentrations of iron oxides are observed from the EDS analysis of the steam treatment as reported by Mazahery et al This suggests that iron oxides formation takes place through oxidizing reaction.…”
Section: Eds Analysis Of the Steam Treatmentsupporting
confidence: 72%
“…4) suggests the presence of magnetite and hematite in the structure. Mazahery et al have reported that ferrous materials have shown the presence of oxides, which is an implication of oxide wear mechanism [33]. In the current study, high concentrations of iron oxides are observed from the EDS analysis of the steam treatment as reported by Mazahery et al This suggests that iron oxides formation takes place through oxidizing reaction.…”
Section: Eds Analysis Of the Steam Treatmentsupporting
confidence: 72%
“…These include cogwheels, piston rings, compressor wings, even space shuttle skin plating, and household objects. More than 90% of world PM materials are iron-based materials (Ciaś, 1992;Mazahery & Shabani, 2012;Missol, 1972). The powder metallurgy route consists mainly of four stages: powders' production, mixing, the compacts fabrication and sintering.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of AL-based metal matrix composite continue to expand for structural applications. Particularly in aerospace and automotive industries, owing to their low density, high thermal conductivity, high specific strength, stiffness, and better wear resistance resulting in considerable economic advantages [2][3][4][5][6][7][8][9]. Aluminum alloy has disadvantages as low hardness and poor wear resistance which are the main obstacles for their high performance tribiological applications [10,11].…”
Section: Introductionmentioning
confidence: 99%